?EFFECT OF ALKALI AND HIGH PRESSURE STEAM TREATMENTS OF RICE STRAW ON CHEMICAL COMPOSITION ANDIN SITU DEGRADABILITY - REHMAN, ZIA-UR-; SHAH, W.H. (Biological Sciences - PJSIR, 1995)
The effect of sodium carbonate, sodium bicarbonate and high pressure ’steam treatment on chemical composition and in situ degradability of rice straw were studied. In situ organic matter degradability of untreated rice straw was 33.3% whereas it increased to 42.8% after steam/pressure treatment. However, organic matter degradability of rice straw on treatment with NaHC03 and NazC03 and steam under pressure increased degradability upto 66.1 %. Improve- ment in the degradability of cellulose was also observed as a result of these treatments. Silica and lignin contents of rice straw were partially removed on treatment with both of these alkalies. The combined treatment of alkali and steam was found to be most effective in reducing silica and lignin contents of rice straw. After these treatments, three fold increase in reducing sugars was observed due to reduction in hemicellulose. , ,